(untitled) (Journal of Asian Development Studies, 2024)
Water disputes between India and Pakistan revolve around river basins and are rooted in the region’s geography, shared history, and culture. Tensions about water issues in South Asia have escalated significantly due to the deteriorating relations between Pakistan and India, stemming from India’s inequitable practices in water allocation. Pakistan and India engaged in conflict over the Indus basin rather than negotiating the 1960 Indus Waters Treaty, which both nations have upheld for over 63 years despite two wars and the nuclear age. The water issue between India and Pakistan is a protracted conflict that worsens each day. The presence of nuclear arsenals in the region has added to the volatility of water disputes. This situation requires that water conflicts between Pakistan and India be studied, and possible alternate options and strategies may be explored to lessen the intensity of the water conflicts between Pakistan and India. Thus, the study examined the water disputes between the two countries. The hydrohegemony framework was put in to understand the water disputes between India and Pakistan because India lands in the graph of negative hegemony. The study suggests that both countries’ water management should have feasible regional arrangements